Дослідження руху часток зернового матеріалу у вертикальному каналі пневмогравітаційного класифікатора - Котов, Б. І.; Степаненко, С. П.; Котов, Б. И.; Kotov, B.; Stepanenko, S. (ЦНТУ, 2019)
В статті розглядається підвищенні ефективності фракціонування зернових сумішей у пневматичних протоках кругового поперечного перерізу, шляхом визначення раціональної форми та параметрів подачі матеріалу, а також форми пневматичного каналу та варіантів розвантаження фракцій. Отримано закономірності зміни швидкості руху та траєкторії матеріалу в пневматичних каналах круглого перетину з нижнім вивантаженням. Закономірності руху частинок у вигляді матеріальної точки вздовж поверхні живильної фази визначили з урахуванням сил опору повітря, сил тертя, вологості та щільності матеріалу на основі теоретичного вивчення процесу фракціонування суміші зерна в пневматичних каналах кругового поперечного перерізу. Використовуючи запропоновані формули для проектування сепараторів повітря, можна визначити початкову швидкість і напрямок входження частинок у повітряний потік, що є початковими умовами для визначення траєкторії матеріалу в повітряних каналах круглого перетину з нижнім вивантаженням. В статье рассматривается повышении эффективности фракционирования зерновых смесей в пневматических протоках кругового поперечного сечения, путем определения рациональной формы и параметров подачи материала, а также формы пневматического канала и вариантов разгрузки фракций. Получены закономерности изменения скорости движения и траектории материала в пневматических каналах круглого сечения с нижнейвыгрузкой.Закономерности движения частиц в виде материальной точки вдоль поверхности питательной фазы определили с учетом сил сопротивления воздуха, сил трения, влажности и плотности материала на основе теоретического изучения процесса фракционирования смеси зерна в пневматических каналах кругового поперечного сечения. Используя предложенные формулы для проектирования сепараторов воздуха, можно определить начальную скорость и направление вхождения частиц в воздушный поток, которые являются исходными условиями для определения траектории материала в воздушных каналах круглого сечения с нижней выгрузкой. The separation of grain mixtures into fractions by aerodynamic characteristics allows to increase the level of purity of the basic material - grains, seeds, etc., that is, to obtain a product with a given level of quality. The article discusses increasing the efficiency of fractionation of grain mixtures in pneumatic ducts of circular cross section by determining the rational shape and parameters of the material supply, as well as the shape of the pneumatic channel and options for unloading fractions. Based on the use of aerodynamic provisions, an original mathematical model of the process of moving the particles introduced at an angle to the vertical pneumatic channel was created. The proposed model takes into account the logarithmic irregularity of the air velocity field plot. A number of assumptions have been made: air turbulent mode, the resistance of the particle is proportional to the square of its relative velocity, the particles do not interact with other particles and the walls of the channel, while rotating at a constant speed. Regularities of the change in the speed of movement and the trajectory of the material in pneumatic channels of circular cross section with lower discharge are obtained. The patterns of particle motion in the form of a material point along the surface of the nutrient phase were determined taking into account the air resistance forces, friction forces, humidity and density of the material based on a theoretical study of the fractionation of a grain mixture in pneumatic channels of circular cross section. On the basis of theoretical studies, taking into account the deflection forces of Zhukovsky and Magnus, the possibility of separating particles of grain material into fractions by aerodynamic properties in vertical channels with lower discharge was determined. The use of airflow as a separating carrier can significantly increase the magnitude of the delineation of trajectories and the criterion of separation of grain into fractions. Simplified mathematical models of motion of components of grain material in air separators with vertical channels allow to determine the rational modes of operation of new technical means.
Исследование движения частиц зернового материала в вертикальных каналах пневмогравитационного классификатора
Investigation of the Movement of Particles of Grain Material in the Vertical Channels of the Pneumogravitational Classifier
Keywords: потік повітря; змінна швидкість повітря; траєкторія; стійкість сил; фракції; процес фракціонування; суміш зерна; повітряний сепаратор; пневматичний круговий потік; поток воздуха; переменная скорость воздуха; траектория; устойчивость сил; фракции; процесс фракционирования; смесь зерна; воздушный сепаратор; пневматический круговой поток; air flow; variable air speed; trajectory; stability of forces; fractions; fractionation process; grain mixture; air separator; pneumatic circular flow